S tebou a bez teba: Antológia súčasnej slovenskej ľúbostnej poézie - Horov, Pavol, 1914-1975; Kostra, Ján, 1910-1975; Mihálik, Vojtech, 1926-2001; Rúfus, Milan, 1928-2009; Smrek, Ján, 1898-1982; Válek, Miroslav, 1927-1991; Žáry, Štefan, 1918-2007 (Máj, 1966)
V tomto výbere nájdeme ľúbostné básne.